Multisectoral practices supporting deaf learners’ academic performance at an inclusive school in Lesotho - Ntloyalefu Palime; Kananga Robert Mukuna (International Journal of Studies in Psychology)
This study explores the relative importance of multisectoral practices from an inclusive school in Lesotho. This study adopted a qualitative approach through a transformative paradigm and participatory design. Thirty-four participants were purposively selected: teachers, sign language interpreters, hearing learners, deaf learners, and heads of departments at an inclusive school in the Leribe district, Lesotho. It employed focus group discussions and collages as instruments for data generation. The findings indicated that multisectoral practices such as the Ministry of Education, non-governmental organisations, neighbouring schools, health centres, and higher education institutions could be the external sources to enhance the academic performance of DLs. This study recommends separate stakeholders work together and accomplish a joint mission through communication.